The Banach-Mazur game and products of Baire spaces - Medina, Gabriel Andre Asmat (2020)
In this work we study Baire spaces and analyze the problem of product of Baire spaces. Then we present some conditions using the Banach-Mazur game to show that the Baire product is preserved in the product. Then we analyze the difference of the infinite product of Baire spaces, between the box product and Tychonoff product. We also present a multiboard version for this problem. Finally we present some open problems regarding the product of Baire spaces.